2018
DOI: 10.1373/clinchem.2018.293480
|View full text |Cite
|
Sign up to set email alerts
|

Brain Natriuretic Peptide in Plasma as Predictor of All-Cause Mortality in a Large Danish Primary Health Care Population Suspected of Heart Failure

Abstract: BACKGROUND Measurement of B-type natriuretic peptide (BNP) in plasma may have its greatest potential in primary care, as general practitioners need to rapidly identify patients who warrant further medical review. The aim of the present study was to examine the prognostic information of BNP measurement on all-cause mortality in a large Danish primary care cohort. METHODS This study covered a cohort of Danish primary care patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“… 29 In a primary health-care population suspected of heart failure, we have shown that brain natriuretic peptide in plasma is a valid predictor of all-cause mortality. 30 …”
Section: Resultsmentioning
confidence: 99%
“… 29 In a primary health-care population suspected of heart failure, we have shown that brain natriuretic peptide in plasma is a valid predictor of all-cause mortality. 30 …”
Section: Resultsmentioning
confidence: 99%